MANUCU: A Case Study of Pain Experience Among Elderly as Gout Arthritis Sufferer in Tomohon City - Nusawakan, Arwyn Weynand; Nugroho, Kristiawan Prasetyo Agung; Rottie, Marselina Ireine (Indonesian Journal of Global Health Research, 2024)
Gout Arthritis is a degenerative disease caused by the deposit of monosodium urate crystals in joints and triggered acute inflammation. One of the most dramatic events occurring to GA sufferers is a flare, a severe condition that rises quickly and lasts for one or two weeks. The pain's intensity and subjective experience vary between individuals and could be among groups. Therefore, identifying how the sufferer expresses pain is essential to understanding the phenomenon. Objective: This study aimed to explore the pain experience of GA Sufferers. Methods: A single case study was applied to conduct this qualitative research. This research was located in Tomohon City and occurred in September 2024. In-dept interviews were done with three adults who are GA sufferers. A narrative analysis of each participant was used to describe the result. Results: Participants are polyarticular tophaceous gout sufferers. Participant 1 (P1) expresses his pain as "ba’-nyut-nyut" or "manucu" (the pain was excruciating, like being stabbed with a needle), burns, and even makes him cannot wake up from bed due to the painful feeling and the foot tophi. Meanwhile, P2 says the Manucu experience usually happens during cold temperatures and makes him totofore (trembling). Last, the third participant says it feels like being stabbed, "ba-cucuk," and very painful. Conclusions: Pain is a subjective experience of the sufferer and has impact in his/her quality of life however, pain is also expressed in a commonality based on the sufferer cultural background like the word "manucu" exists as a characteristic of the pain in the community.